Sports Massage Understanding Survey on Students Sports Coaching Study Program at Muhammadiyah University of Bone - Faturahman, M.; Darminto, Andi Ogo; Santos, Maria Herlinda Dos (S&Co Publishing, 2023)
This research is a quantitative research that aims to determine the level of understanding of student learning in the Super Massage course in the Sports Coaching Education Study Program using a questionnaire distribution instrument to 45 respondents from batch 1 and 2 students. Data Collection Techniques by distributing questionnaires (google Forms). The collected data is then processed in a quantitative descriptive way using the Likert method. From the existing research, it was found that from 45 respondents it turned out that there was 1 respondent 2.22% included in the very good category, 10 respondents 22.22% in the good category, 20 respondents 44.44% in the category quite good, 11 respondents 24.44% of respondents were in the unfavorable category and 3 respondents were in the unfavorable category. So it was concluded that each respondent occupied each category but the respondents were more dominant in the fairly good category.